Kebijakan Pemberhentian Ekspor Biji Nikel Indonesia Tahun 2020: Tinjauan Neomerkantilisme - Novi Ratna Cahyani (Jayapangus Press, 2023)
The utilization of nickel ore has increased along with the growing trend of electric vehicles. As a country with abundant nickel ore resources, Indonesia has received economic benefits from nickel ore export activities. However, since January 1, 2020, Indonesia has taken a policy to stop the export of nickel ore. Indonesia’s decision is interesting to study for two reasons. First, a ban on nickel ore exports has reduced state revenues. Second, the policy of stopping nickel ore exports creates a bad perception from partner countries that have depended on the supply of raw materials. This research aims to examine why Indonesia implemented the policy of stopping nickel ore exports in 2020. This research explores existing problems using a neomercantilism perspective through qualitative research methods with secondary data sources. The results show that stopping the export of nickel ore is Indonesia's neomercantilist policy to secure the supply of nickel ore and support domestic companies BUMN, to increase their relative position in international trade. It was concluded that stopping nickel ore exports in 2020 had improved Indonesia's relative position in international trade.